Implementation of Music Copyright Protection Policy in the Era of Digital Transformation at the Ministry of Law and Human Rights - Selvira, Rizka; Izzatusolekha; Salam, Rahmat (Global Writing Academica Researching & Publishing, 2024)
The implementation of music copyright protection policies has experienced significant shifts during the digital transformation. Digitalization impacts the economy, society, and government services, creating gaps that can render policies irrelevant. In the music industry, the proliferation of pirated content harms not only creators but also the country's creative sector. This research aims to address copyright protection for songwriters amid digitalization and the challenges in enforcing copyright law. Using qualitative descriptive methods, the study hypothesizes that certain underlying factors contribute to the failure of copyright enforcement. Results, analyzed through Van Meter and Van Horn's theory, reveal weaknesses in ambiguous policy standards, inadequate examination by policymakers, non-compliance with SOPs by implementing organizations, and a lack of synchronization among stakeholders, leading to ineffective enforcement and weak government protection for copyright holders. Therefore, it is essential to conduct factual studies to reassess standards, involved organizations, and active stakeholders in policy implementation. Expanding regional and national initiatives through workshops to raise public awareness about copyright is crucial, alongside comprehensive socialization efforts targeting policymakers, musicians, and consumers.